1996
DOI: 10.1093/ajcp/105.4.430
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Pseudotumors of Lymph Node Origin Show Macrophage-Derived Spindle Cells and Lymphocyte-Derived Cytokine Transcripts Without Evidence of T-Cell Receptor Gene Rearrangements:Implications for Pathogenesis and Classification as an Idiopathic Retroperitoneal Fibrosis-Like Sclerosing Immune Reaction

Abstract: I n f l a m m a t o r y P s e u d o t u m o r s o f L y m p h N o d e O r i g i n S h o w M a c r o p h a g e -D e r i v e d S p i n d l e C e l l s a n d L y m p h o c y t e -D e r i v e d C y t o k i n e T r a n s c r i p t s W i t h o u t E v i d e n c e o fT -C e l l R e c e p t o r G e n e R e a r r a n g e m e n t s Address reprint requests to Dr. Menke: Mayo Clinic Jacksonville, 4500 San Pablo Road, Jacksonville, FL 32224.(KP1) or HAM-56, and HLA-DR (LN3) immunoreactivity and demonstrated production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…Table 2 summarizes the main aspects in the differential diagnoses of IPTlike FDCT. In this context IPT may be also included, as it represents a lesion composed of ovoid to spindle cells admixed with polymorphic inflammatory cells, mostly T lymphocytes, but also B cells, plasma cells and histiocytes [16][17][18]. The nature of spindle cells in these lesions is still challenging because of their phenotypic variability.…”
Section: Differential Diagnosesmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarizes the main aspects in the differential diagnoses of IPTlike FDCT. In this context IPT may be also included, as it represents a lesion composed of ovoid to spindle cells admixed with polymorphic inflammatory cells, mostly T lymphocytes, but also B cells, plasma cells and histiocytes [16][17][18]. The nature of spindle cells in these lesions is still challenging because of their phenotypic variability.…”
Section: Differential Diagnosesmentioning
confidence: 99%
“…Proportion of spindle and inflammatory cell components varied, predominating in some areas or mostly replaced by fibrous content in others. Lesions tended to follow the vascular axis, through the hilum [16,43]. Among the cases in which an etiological agent can be detected, pathologist should search for infection, especially for T. pallidum, as it has been shown that luetic lymphadenitis may also cause lymph node IPT [18,44].…”
Section: Inflammatory Pseudotumor In Lymph Nodes and Spleenmentioning
confidence: 99%
“…Monoclonal T-lymphocytes have been described in inflammatory sclerosing disorders, such as idiopathic retroperitoneal fibrosis [14], which shares some morphological similarities with IPT/IMT. However, they have never been investigated in pancreatic IPT/IMT and have never been found in IPT arising in other anatomical sites [6,28]. The significance and the origin of the clonal T-lymphocytes in this case of IPT/IMT are currently not known, but it can be speculated that they develop in the context of an intense and destructive, maybe also selfstimulating, inflammatory reaction.…”
Section: Discussionmentioning
confidence: 94%
“…Here, we report a case of IPT/ IMT of the pancreas. We further provide a characterization of its cell population, with particular attention paid to the inflammatory cell component, in view of the fact that the inflammatory cells seem to play a fundamental role in the pathogenesis of the lesion through the production of cytokines and growth factors that, in turn, influence the phenotypic characteristics of the spindle cell and connective tissue elements [23,28]. We also discuss the potential relationship between IPT and autoimmune pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its chemotactic potential, transforming growth fac-tor+ as well promotes the production of other growth factors, upregulates the synthesis of extracellular matrix components and expression of cellular integrin receptors, and inhibits the action of proteolytic enzymes that destroy newly formed connective tissue. Consequently, the inflammatory response is enhanced while the proliferation of the collagen-producing cells is boosted (19)(20)(21)(22). This cytokine-initiated and perpetuated cascade-reaction results in certain sclerosing disorders and maybe also portrays the mechanism involved in the pathogenesis of the fasciitis-panniculitis syndromes.…”
Section: Discussionmentioning
confidence: 99%